High-safety diaphragm suitable for fast charging, preparation method of high-safety diaphragm, lithium ion battery and electric equipment
By adopting a three-layer polypropylene structure separator design, combined with heat treatment and stretching technology, the safety hazards of lithium-ion batteries during fast charging are solved, and high safety and fast charging performance are achieved, and lithium-ion is improved. Conductive efficiency and cell circulation capacity retention rate.
Patent Information
- Application Number
- CN202411637500.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-03
AI Technical Summary
The existing lithium-ion battery separators have safety hazards during fast charging. The thin diaphragms have poor heat resistance, which can easily lead to shrinkage of the diaphragm and short-circuit contact with the positive and negative electrodes, making it difficult to take into account high safety and fast charging performance.
The separator design adopts a three-layer polypropylene structure, wherein the thickness, melt index and crystallinity of the first and third polypropylene layers are lower than that of the second polypropylene layer. The composite multi-layer cast film is formed through heat treatment and stretching to improve the separator. The mechanical strength and porosity achieve both high safety and fast charging performance.
The high film breaking temperature and mechanical strength of the diaphragm are achieved, which increases safety. At the same time, the rapid conduction capacity of lithium ions is improved through wide and rich microporous channels, which meets the high-rate charging and discharging performance, and prevents positive performance in the battery cell. The negative electrode material is short-circuited.
Smart Images

Figure CN119253193A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium-ion batteries, and in particular to a high-safety diaphragm suitable for fast charging and a preparation method thereof, a lithium-ion battery and electrical equipment. Background Art
[0002] In recent years, as the demand for increased energy density and fast charging of lithium-ion batteries has become more urgent, more and more domestic diaphragm manufacturers have invested a lot of R&D funds to develop lithium battery diaphragms suitable for current battery cells. In order to solve the current energy density and fast charging problems, the first-line diaphragm manufacturers have reached a consensus to make lithium battery diaphragms lighter and thinner. Thinner diaphragms greatly shorten the path of lithium ion conduction, thereby achieving rapid passage of lithium ions. At the same time, more coating thickness is reserved for the positive and negative electrodes, taking into account higher energy density.
[0003] But the reality is that as the thickness of the diaphragm becomes thinner and thinner, although the diaphragm's dynamics are better and can meet the current needs of fast charging and discharging, it also poses a potential safety hazard: the thinner the base film, the worse its heat resistance. When the battery cell is charged and discharged at a high rate, the temperature rise of the battery cell is large, which can easily lead to the shrinkage of the diaphragm size and direct contact between the positive and negative electrodes, causing a short circuit.
[0004] Therefore, in the direction of diaphragm lightweight technology, choosing high safety or fast charging performance has become a choice that you cannot have both. Summary of the invention
[0005] The purpose of this application is to provide a high-safety diaphragm suitable for fast charging and its preparation method, lithium-ion battery and electrical equipment to solve the above problems.
[0006] To achieve the above objectives, the present application provides, in a first aspect, a high-safety diaphragm suitable for fast charging, comprising a first polypropylene layer, a second polypropylene layer, and a third polypropylene layer;
[0007] The second polypropylene layer is disposed between the first polypropylene layer and the third polypropylene layer;
[0008] The thickness, melt index and crystallinity of the first polypropylene layer and the third polypropylene layer are each independently lower than those of the second polypropylene layer.
[0009] Optionally, the high-safety diaphragm suitable for fast charging satisfies at least one of the following conditions:
[0010] A. The thickness of the first polypropylene layer and the third polypropylene layer are each independently 0.055 times to 0.33 times the thickness of the second polypropylene layer;
[0011] B. the ratio of the melt index of the first polypropylene layer and the third polypropylene layer to the melt index of the second polypropylene layer is independently 1:1.25-5;
[0012] C. The ratio of the crystallinity of the first polypropylene layer and the third polypropylene layer to the crystallinity of the second polypropylene layer is independently 0.92-0.98:1.
[0013] Optionally, the high-safety diaphragm suitable for fast charging satisfies at least one of the following conditions:
[0014] A. The thickness of the first polypropylene layer and the third polypropylene layer are each independently 0.08-0.25 times the thickness of the second polypropylene layer;
[0015] B. the ratio of the melt index of the first polypropylene layer and the third polypropylene layer to the melt index of the second polypropylene layer is independently 1:2-4;
[0016] C. The ratio of the crystallinity of the first polypropylene layer and the third polypropylene layer to the crystallinity of the second polypropylene layer is independently 0.95-0.97:1.
[0017] Optionally, the high-safety diaphragm suitable for fast charging satisfies at least one of the following conditions:
[0018] A. the average radius of the micropores of the first polypropylene layer and the third polypropylene layer are independently 0.5 to 0.93 times the average radius of the micropores of the second polypropylene layer;
[0019] B. The porosity of the first polypropylene layer and the third polypropylene layer is independently 0.6 to 0.95 times the porosity of the second polypropylene layer;
[0020] C. The surface porosity of the first polypropylene layer and the third polypropylene layer is independently 35%-50%;
[0021] D. The pore sizes of the first polypropylene layer and the third polypropylene layer are independently 20 nm to 50 nm.
[0022] Optionally, the average radius of the micropores of the first polypropylene layer and the third polypropylene layer are independently 0.7 to 0.9 times the average radius of the micropores of the second polypropylene layer.
[0023] Optionally, the high-safety diaphragm suitable for fast charging satisfies at least one of the following conditions:
[0024] A. The porosity of the first polypropylene layer and the third polypropylene layer is independently 0.8 to 0.95 times the porosity of the second polypropylene layer;
[0025] B. The surface porosity of the first polypropylene layer and the third polypropylene layer is independently 38%-46%;
[0026] C. The pore sizes of the first polypropylene layer and the third polypropylene layer are independently 20 nm to 35 nm.
[0027] The second aspect of the present application provides a method for preparing a high-safety diaphragm suitable for fast charging, comprising:
[0028] The first polypropylene layer material, the second polypropylene layer material and the third polypropylene layer material are melt-extruded to obtain a composite multi-layer cast film;
[0029] The composite multilayer cast film is heat treated and stretched to obtain a high-safety diaphragm suitable for fast charging.
[0030] Optionally, the method for preparing the high-safety diaphragm suitable for fast charging satisfies at least one of the following conditions:
[0031] A. The heat treatment temperature is 130°C-155°C and the time is 0.5h-3h;
[0032] B. The stretching includes cold drawing, hot drawing and heat setting in sequence;
[0033] The cold drawing temperature is 70°C-95°C, and the speed ratio is 1.02-1.1;
[0034] The temperature of the hot drawing is 130°C-148°C, and the speed ratio is 1.9-2.2;
[0035] The temperature of the heat setting is 153° C.-160° C., and the speed ratio is 0.9-0.97.
[0036] The third aspect of the present application provides a lithium-ion battery, comprising the high-safety diaphragm suitable for fast charging or the high-safety diaphragm suitable for fast charging prepared by the preparation method of the high-safety diaphragm suitable for fast charging.
[0037] A fourth aspect of the present application provides an electrical device comprising the lithium-ion battery.
[0038] Compared with the prior art, the beneficial effects of this application include:
[0039] The high-safety diaphragm suitable for fast charging provided in the present application takes into account both the high safety and fast charging performance of the diaphragm by setting a three-layer polypropylene layer structure and limiting the different melting indexes, crystallinity and thickness of the inner layer and the surface layer; wherein, the melting index of the first polypropylene layer and the third polypropylene layer is lower than that of the second polypropylene layer, so as to achieve the low melting index characteristics of the outer layer, so as to achieve a higher melting point and molecular weight of the surface layer, so that the diaphragm has a higher film breaking temperature and mechanical strength, and the safety of the diaphragm is increased; the crystallinity of the first polypropylene layer and the third polypropylene layer is lower than that of the second polypropylene layer, so as to achieve a higher porosity and a larger microporous structure of the core layer, and the wide and abundant microporous channels can realize the rapid conduction of lithium ions, giving the battery cell better fast charging capability and lower membrane surface impedance; the thickness of the first polypropylene layer and the third polypropylene layer is lower than that of the second polypropylene layer, and on the premise of ensuring that the surface layer of the diaphragm has good puncture resistance and tensile strength, the transmission distance of lithium ions in the first polypropylene layer and the third polypropylene layer with relatively fewer micropores and smaller micropores is reduced, thereby achieving a fast charging effect.
[0040] The present application provides a method for preparing a high-safety diaphragm suitable for fast charging. First, the second polypropylene layer is made of a polypropylene material with high crystallinity and high melt index. The material has excellent processing fluidity after high-temperature melting, and the lamellae are thicker and longer after film formation. Therefore, under the same high-ratio stretching, the core layer can form a higher porosity and a larger microporous structure. The broad and abundant microporous channels can realize the rapid conduction of lithium ions, giving the battery cell better fast charging capability and lower membrane surface impedance; secondly, the first polypropylene layer and the third polypropylene layer are made of materials with low melt index and low crystallinity. The low melt index determines that the core layer has a higher melting point and molecular weight, giving the diaphragm a higher film breaking temperature and mechanical strength; at the same time, the material has poor fluidity after melting and crystallization ability after melt annealing. Since the low melt index polypropylene material has a higher molecular weight and higher crystallization energy, the thickness of the lamellae after film formation is thinner and shorter. Therefore, when stretched at the same heat treatment temperature and ratio, the porosity formed on the surface is slightly lower than the conventional level. The high molecular weight polypropylene material has a stronger tensile strength, so the degree of lamellae separation is lower, and a smaller microporous structure is formed after stretching, which is beneficial to prevent the risk of self-discharge due to large internal pores.
[0041] The lithium-ion battery provided by the present application uses the fast-charging high-safety diaphragm, which has high anti-puncture strength. When a battery collision occurs or lithium dendrites or sodium dendrites appear inside the battery, the diaphragm puncture can be prevented from causing the positive and negative electrode materials to short-circuit and heat up, so the battery cell has high safety. At the same time, the characteristics of the diaphragm give the battery high-rate charge and discharge performance.
[0042] The electrical equipment provided in this application, equipped with the lithium-ion battery provided in this application, can output or input a large current and power in a short period of time to meet high-rate application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0044] Figure 1 This is a schematic diagram of the structure of a high-safety diaphragm suitable for fast charging prepared in Example 1. DETAILED DESCRIPTION
[0045] As used herein:
[0046] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0047] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0048] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0049] In these examples, parts and percentages are by mass unless otherwise indicated.
[0050] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0051] “And / or” is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0052] In a first aspect, the present application provides a high-safety diaphragm suitable for fast charging, comprising a first polypropylene layer, a second polypropylene layer, and a third polypropylene layer;
[0053] The second polypropylene layer is disposed between the first polypropylene layer and the third polypropylene layer;
[0054] The thickness, melt index and crystallinity of the first polypropylene layer and the third polypropylene layer are each independently lower than those of the second polypropylene layer.
[0055] In some embodiments, the high-safety diaphragm suitable for fast charging satisfies at least one of the following conditions:
[0056] A. The thickness of the first polypropylene layer and the third polypropylene layer are each independently 0.055 times to 0.33 times the thickness of the second polypropylene layer;
[0057] Optionally, the thickness of the first polypropylene layer and the third polypropylene layer may be independently 0.055 times, 0.1 times, 0.2 times, 0.3 times, 0.33 times, or any value between 0.055 times and 0.33 times the thickness of the second polypropylene layer;
[0058] It should be noted that when the thickness of the first polypropylene layer and the third polypropylene layer is 0.055 times lower than the thickness of the second polypropylene layer, the overall puncture strength of the diaphragm decreases rapidly, and the battery cell assembled using the diaphragm is prone to poor K value; when the thickness of the first polypropylene layer and the third polypropylene layer is 0.33 times higher than the thickness of the second polypropylene layer, the air permeability of the diaphragm increases rapidly, the dynamics deteriorate, and the fast charging effect is lost;
[0059] B. the ratio of the melt index of the first polypropylene layer and the third polypropylene layer to the melt index of the second polypropylene layer is independently 1:1.25-5;
[0060] Optionally, the ratio of the melt index of the first polypropylene layer and the third polypropylene layer to the melt index of the second polypropylene layer can be independently 1:1.25, 1:2, 1:3, 1:4, 1:5 or any value between 1:1.25-5;
[0061] It should be noted that the ratio of the melt index of the first polypropylene layer and the third polypropylene layer to the melt index of the second polypropylene layer is independently 1:1.25-5. The first polypropylene layer and the third polypropylene layer have lower melt indexes, which can give the diaphragm surface stronger puncture strength and tensile strength, ensure that the surface pore size is smaller, and improve the self-discharge problem in the industry; relatively, the second polypropylene layer has a higher melt index, and the lamellae formed in the casting process are wider and thicker, and the pore size is larger, which can ensure the rapid transmission of lithium ions in the micropores;
[0062] C. The ratio of the crystallinity of the first polypropylene layer and the third polypropylene layer to the crystallinity of the second polypropylene layer is independently 0.92-0.98:1.
[0063] Optionally, the ratio of the crystallinity of the first polypropylene layer and the third polypropylene layer to the crystallinity of the second polypropylene layer can independently be 0.92:1, 0.93:1, 0.94:1, 0.95:1, 0.96:1, 0.97:1, 0.98:1 or any value between 0.92-0.98:1.
[0064] It should be noted that when the ratio of the crystallinity of the first polypropylene layer and the third polypropylene layer to the crystallinity of the second polypropylene layer is independently 0.92-0.98:1, during the stretching pore-forming process, the crystallinity of the first polypropylene layer and the third polypropylene layer is relatively low, and the pore-forming is characterized by small and large micropores, which can improve the self-discharge problem; the second polypropylene layer has a higher crystallinity, and the pore-forming is characterized by large and large micropores, which is more suitable for rapid lithium ion transmission.
[0065] In some embodiments, the high-safety diaphragm suitable for fast charging satisfies at least one of the following conditions:
[0066] A. The thickness of the first polypropylene layer and the third polypropylene layer are each independently 0.08-0.25 times the thickness of the second polypropylene layer;
[0067] Optionally, the thickness of the first polypropylene layer and the third polypropylene layer may be independently 0.08 times, 0.1 times, 0.15 times, 0.2 times, 0.25 times, or any value between 0.08 and 0.25 times the thickness of the second polypropylene layer;
[0068] B. the ratio of the melt index of the first polypropylene layer and the third polypropylene layer to the melt index of the second polypropylene layer is independently 1:2-4;
[0069] Optionally, the ratio of the melt index of the first polypropylene layer and the third polypropylene layer to the melt index of the second polypropylene layer can be independently 1:2, 1:3, 1:4 or any value between 1:2-4;
[0070] C. The ratio of the crystallinity of the first polypropylene layer and the third polypropylene layer to the crystallinity of the second polypropylene layer is independently 0.95-0.97:1.
[0071] Optionally, the ratio of the crystallinity of the first polypropylene layer and the third polypropylene layer to the crystallinity of the second polypropylene layer can independently be 0.95:1, 0.955:1, 0.965:1, 0.97:1 or any value between 0.95-0.97:1.
[0072] In some embodiments, the high-safety diaphragm suitable for fast charging satisfies at least one of the following conditions:
[0073] A. the average radius of the micropores of the first polypropylene layer and the third polypropylene layer are independently 0.5 to 0.93 times the average radius of the micropores of the second polypropylene layer;
[0074] Optionally, the average pore radius of the first polypropylene layer and the third polypropylene layer can independently be 0.5 times, 0.6 times, 0.7 times, 0.8 times, 0.93 times, or any value between 0.5 times and 0.93 times the average pore radius of the second polypropylene layer;
[0075] It should be noted that the size of the average radius of the micropores is regulated by the melt index. When the average radius of the micropores of the first polypropylene layer and the third polypropylene layer is independently 0.5 to 0.93 times the average radius of the micropores of the second polypropylene layer, the larger micropores of the second polypropylene layer can achieve rapid lithium ion conduction, and the first polypropylene layer and the third polypropylene layer are relatively small micropores, which can prevent the problem of excessive self-discharge of the diaphragm.
[0076] B. The porosity of the first polypropylene layer and the third polypropylene layer is independently 0.6 to 0.95 times the porosity of the second polypropylene layer;
[0077] Optionally, the porosity of the first polypropylene layer and the third polypropylene layer may be independently 0.6 times, 0.7 times, 0.8 times, 0.95 times, or any value between 0.6 times and 0.95 times the porosity of the second polypropylene layer;
[0078] It should be noted that by regulating the porosity through crystallinity, when the porosity of the first polypropylene layer and the third polypropylene layer is independently 0.6 to 0.95 times that of the second polypropylene layer, the second polypropylene layer can provide more lithium ion transmission channels and larger electrolyte storage space, thereby improving the lithium ion transmission efficiency;
[0079] C. The surface porosity of the first polypropylene layer and the third polypropylene layer is independently 35%-50%;
[0080] Optionally, the surface porosity of the first polypropylene layer and the third polypropylene layer may be independently 35%, 40%, 45%, 50% or any value between 35% and 50%;
[0081] D. The pore sizes of the first polypropylene layer and the third polypropylene layer are independently 20 nm to 50 nm.
[0082] Optionally, the pore sizes of the first polypropylene layer and the third polypropylene layer may be independently 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm or any value between 20 nm and 50 nm.
[0083] In some embodiments, the average radius of the micropores of the first polypropylene layer and the third polypropylene layer are independently 0.7 to 0.9 times the average radius of the micropores of the second polypropylene layer.
[0084] Optionally, the average radius of the micropores of the first polypropylene layer and the third polypropylene layer may independently be 0.7 times, 0.8 times, 0.9 times, or any value between 0.7 times and 0.9 times the average radius of the micropores of the second polypropylene layer.
[0085] In some embodiments, the high-safety diaphragm suitable for fast charging satisfies at least one of the following conditions:
[0086] A. The porosity of the first polypropylene layer and the third polypropylene layer is independently 0.8 to 0.95 times the porosity of the second polypropylene layer;
[0087] Optionally, the porosity of the first polypropylene layer and the third polypropylene layer may be independently 0.8 times, 0.85 times, 0.9 times, 0.95 times, or any value between 0.8 times and 0.95 times the porosity of the second polypropylene layer;
[0088] B. The surface porosity of the first polypropylene layer and the third polypropylene layer is independently 38%-46%;
[0089] Optionally, the surface porosity of the first polypropylene layer and the third polypropylene layer may be independently 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46% or any value between 38% and 46%;
[0090] C. The pore sizes of the first polypropylene layer and the third polypropylene layer are independently 20 nm to 35 nm.
[0091] Optionally, the pore sizes of the first polypropylene layer and the third polypropylene layer may independently be 20 nm, 22 nm, 24 nm, 26 nm, 28 nm, 30 nm, 32 nm, 34 nm, 35 nm or any value between 20 nm and 35 nm.
[0092] The second aspect of the present application provides a method for preparing a high-safety diaphragm suitable for fast charging, comprising:
[0093] The first polypropylene layer material, the second polypropylene layer material and the third polypropylene layer material are melt-extruded to obtain a composite multi-layer cast film;
[0094] The composite multilayer cast film is heat treated and stretched to obtain a high-safety diaphragm suitable for fast charging.
[0095] It should be noted that the surface materials such as the first polypropylene layer material and the third polypropylene layer material are all low melt index materials with higher molecular weight and melting point, so the tensile strength and film breaking temperature of the surface layer are higher, while the melt index and crystallinity of the second polypropylene layer (core layer) material are higher. The cast film formed after extrusion casting has higher crystallinity, and the thickness and length of the lamellae are larger. Therefore, when stretched under high magnification conditions, its porosity is higher and the micropore diameter is larger; it can be understood that the melt index and crystallinity of the surface layer material and the core layer material are different, and the difference in the lamellae of the cast film can be achieved. After further heat treatment and stretching, the surface layer with a smaller melt index, relatively lower crystallinity and relatively thin lamellae thickness forms a relatively small micropore diameter, and the porosity is relatively low; on the contrary, the material of the core layer has a higher melt index and crystallinity. After further heat treatment and the same high stretching ratio, the core layer with high crystallinity and wider and thicker lamellae forms a relatively large micropore diameter and a higher porosity, which can provide sufficient space for electrolyte storage and provide wider and more ion channels.
[0096] In some embodiments, a cast film is prepared using a cast extruder having a dual extruder, a distributor, and a three-layer co-extrusion die head, core layer polypropylene particles with a higher melt index and a higher crystallinity are added to the main extruder, and surface layer polypropylene particles with a low melt index and a relatively low crystallinity are added to the auxiliary extruder. The two materials are melt-extruded into the distributor and the three-layer die head by the screw, respectively, wherein the middle melt of the die head is a low melt index melt and the outer layer melt is a high melt index melt. It can be understood that the extrusion amount W of the high melt index polypropylene melt in the main extruder is 1 The extrusion volume W of the low melt index polypropylene melt of the auxiliary extruder 2 The total amount determines the total thickness of the diaphragm. The ratio of the extrusion amount of the low melt index polypropylene melt of the auxiliary extruder to the extrusion amount of the high melt index polypropylene melt of the main extruder determines the ratio of the thickness of the surface layer and the core layer of the new diaphragm. Furthermore, the melt index ratio of the polypropylene particles of the main extruder and the polypropylene particles of the auxiliary extruder determines the ratio of the micropore diameters of the surface layer and the core layer.
[0097] In some embodiments, the method for preparing a high-safety diaphragm suitable for fast charging satisfies at least one of the following conditions:
[0098] A. The heat treatment temperature is 130°C-155°C and the time is 0.5h-3h;
[0099] Optionally, the heat treatment temperature may be 130°C, 135°C, 140°C, 145°C, 150°C, 155°C or any value between 130°C and 155°C, and the heat treatment time may be 0.5h, 1h, 2h, 3h or any value between 0.5h and 3h;
[0100] It should be noted that heat treatment at 130°C-155°C causes the core layer and the surface layer to further grow, increase and thicken.
[0101] B. The stretching includes cold drawing, hot drawing and heat setting in sequence;
[0102] It should be noted that stretching is the film-forming process, in which the heat-treated cast film is stretched on a dry unidirectional stretching machine to obtain a high-safety diaphragm suitable for fast charging, which has small-diameter micropores on the surface and large-diameter micropores in the core layer.
[0103] The cold drawing temperature is 70°C-95°C, and the speed ratio is 1.02-1.1;
[0104] Optionally, the cold drawing temperature may be 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or any value between 70°C and 95°C, and the speed ratio may be 1.02, 1.04, 1.06, 1.08, 1.1 or any value between 1.02 and 1.1;
[0105] The temperature of the hot drawing is 130°C-148°C, and the speed ratio is 1.9-2.2;
[0106] Optionally, the temperature of the hot drawing may be 130° C., 133° C., 136° C., 139° C., 142° C., 145° C., 148° C., or any value between 130° C. and 148° C., and the speed ratio may be 1.9, 2, 2.1, 2.2, or any value between 1.9 and 2.2;
[0107] The temperature of the heat setting is 153° C.-160° C., and the speed ratio is 0.9-0.97.
[0108] Optionally, the heat setting temperature can be 153°C, 156°C, 158°C, 160°C or any value between 153°C and 160°C, and the speed ratio can be 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97 or any value between 0.9 and 0.97.
[0109] The third aspect of the present application provides a lithium-ion battery, comprising the high-safety diaphragm suitable for fast charging or the high-safety diaphragm suitable for fast charging prepared by the preparation method of the high-safety diaphragm suitable for fast charging.
[0110] A fourth aspect of the present application provides an electrical device comprising the lithium-ion battery.
[0111] It should be noted that electrical equipment includes, but is not limited to, one or more of electric vehicles, electric bicycles, smart home devices, robots, heavy trucks, ships, and energy storage systems.
[0112] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0113] Example 1
[0114] A first aspect of the present embodiment provides a high-safety diaphragm suitable for fast charging, comprising a first polypropylene layer, a second polypropylene layer, and a third polypropylene layer stacked in sequence;
[0115] The total thickness of the separator is 12 μm, and the first polypropylene layer and the third polypropylene layer D 1 The thickness of the second polypropylene layer D is 1 μm. 2 The thickness is 10 μm.
[0116] A second aspect of this embodiment provides a method for preparing a high-safety diaphragm suitable for fast charging, comprising:
[0117] S1: Select a cast extruder with a dual extruder, a distributor and a three-layer co-extrusion die head, and add a melt index P 1 The first polypropylene pellets with a melting index of 3 g / min and a crystallinity of 98% are added to the auxiliary extruder. 2 The second polypropylene particles are 1.5 g / min and 95% crystallinity. The two materials are weighted by weight of the second polypropylene particles / the first polypropylene particles = W 2 / W 1 =0.2, two different polypropylene particles are melt-extruded into a distributor and a three-layer die head by a screw, wherein the melt of the middle die head is a first polypropylene particle with a high melt index, and the melt of the surface die head is a second polypropylene particle with a low melt index, to obtain a melt with a three-layer structure, and under the cooling and traction of an annealing roller, a 14.5μm cast film with different oriented crystallization of the core layer and the surface layer is obtained;
[0118] S2: The cast film is placed in an oven at 145°C for baking for 1 hour, so that the core layer and the surface layer lamellae grow further and become perfect;
[0119] S3: The heat-treated cast film is stretched on a dry unidirectional stretching machine, and undergoes cold drawing, hot drawing and heat setting respectively, wherein the cold drawing temperature is 80°C, and the cold drawing speed ratio is 1.04; the hot drawing temperature is 145°C, and the hot drawing speed ratio is 1.9; the heat setting temperature is 158°C, and the heat setting speed ratio is 0.92, to obtain a 12μm high-safety diaphragm suitable for fast charging with a three-layer structure.
[0120] The structural schematic diagram of the high-safety diaphragm suitable for fast charging is shown in Figure 1 shown.
[0121] The third aspect of the present application provides a lithium-ion battery, including the button battery assembled from the above-mentioned high-safety diaphragm suitable for fast charging, wherein the positive electrode material slurry includes lithium iron phosphate: conductive agent: binder: dispersant = 92.14wt%: 3.50wt%: 4.00wt%: 0.36wt%; the negative electrode material is artificial graphite; the electrolyte LiPF 6 The concentration is 1 mol / L, EC:EMC:DMC=1:1:1.
[0122] Example 2
[0123] The difference from Example 1 is: mass ratio of the second polypropylene particle / the first polypropylene particle = W 2 / W 1 =0.11, the first polypropylene layer and the third polypropylene layer D1 The thickness of the second polypropylene layer D is 0.6 μm. 2 The thickness is 10.8 μm.
[0124] Example 3
[0125] The difference from Example 1 is: mass ratio of the second polypropylene particle / the first polypropylene particle = W 2 / W 1 =0.66, the first polypropylene layer and the third polypropylene layer D 1 The thickness of the second polypropylene layer D is 2.4 μm. 2 The thickness is 7.2 μm.
[0126] Example 4
[0127] The difference from Example 1 is: Melt index P 2 is 2.4.
[0128] Example 5
[0129] The difference from Example 1 is: Melt index P 2 is 0.6.
[0130] Example 6
[0131] The difference from Example 1 is that the crystallinity of the second polypropylene particles is 96%.
[0132] Example 7
[0133] The difference from Example 1 is that the crystallinity of the second polypropylene particles is 90%.
[0134] Comparative Example 1
[0135] The difference from Example 1 is: mass ratio of the second polypropylene particle / the first polypropylene particle = W 2 / W 1 =0.8, the first polypropylene layer and the third polypropylene layer D 1 The thickness of the second polypropylene layer D is 3.7 μm. 2 The thickness is 4.6 μm.
[0136] Comparative Example 2
[0137] The difference from Example 1 is: Melt index P 2 is 2.7.
[0138] Comparative Example 3
[0139] The difference from Example 1 is that the crystallinity of the first polypropylene particles is 95%.
[0140] Comparative Example 4
[0141] The difference from Comparative Example 1 is: Melt index P 2 The crystallinity of the first polypropylene particles is 95%, and the crystallinity of the second polypropylene particles is 90%.
[0142] Comparative Example 5
[0143] The difference from Comparative Example 1 is: a 12 μm dry-process diaphragm prepared by a mainstream single-screw single extruder on the market.
[0144] Comparative Example 6
[0145] The difference from Comparative Example 1 is: a 12 μm three-layer co-extruded polypropylene diaphragm is prepared by the method of Patent No. CN113809474A, the mass fraction of the second polypropylene layer is 50wt%, and the melt index of the second polypropylene layer is 0.5g / min; the mass fractions of the first polypropylene layer and the third polypropylene layer are both 25wt%, and the melt indexes are both 8.0g / min.
[0146] Comparative Example 7
[0147] The difference from Comparative Example 1 is that the first polypropylene layer and the third polypropylene layer are both replaced by the second polypropylene layer.
[0148] Comparative Example 8
[0149] The difference from Comparative Example 1 is that the third polypropylene layer is replaced by the second polypropylene layer.
[0150] Comparative Example 9
[0151] The difference from Comparative Example 1 is that the second polypropylene layer is replaced by the third polypropylene layer.
[0152] The relevant parameters of the diaphragm and the preparation method thereof in the embodiments and comparative examples are shown in Table 1, wherein P 1 is the melt index of the first polypropylene particle (unit: g / min); 2 is the melt index of the second polypropylene particle (unit: g / min); 1 / P 2 W is the ratio of the melt index of the first polypropylene particle to the melt index of the second polypropylene particle; 2 / W 1 = mass of the second polypropylene particle / mass of the first polypropylene particle; D 1 is the thickness of the first polypropylene layer and the third polypropylene layer (unit: μm); D 2 is the thickness of the second polypropylene layer (unit: μm).
[0153] Table 1 Related parameters
[0154]
[0155]
[0156] The lithium-ion batteries prepared in the above embodiments and comparative examples were subjected to performance tests such as membrane surface resistance, membrane rupture temperature, liquid absorption rate, soft-pack battery K value, and room temperature cycle retention rate (500 weeks). The data are shown in Table 2.
[0157] Diaphragm surface resistance test: Cut 4 circular diaphragm samples with a diameter of 50mm, place them in the electrolyte, and seal and soak for 1h. Put the 4 diaphragm samples into the test mold in turn, use the electrochemical workstation to measure, and read the resistance values R1, R2, R3, and R4. Surface resistance calculation: Use the number of layers as the horizontal coordinate and the corresponding resistance values of different numbers of layers as the vertical coordinate to draw a graph, and find the slope A of the curve. The sample surface resistance value R=AS, where S is the effective electrode area of the test.
[0158] Film rupture temperature test: Cut a circular diaphragm sample with a diameter of 50mm, seal it in a mold filled with conductive liquid, put the mold with the sample into an oven, heat it at a rate of 5℃ / min, and record the change of the internal resistance in the mold with the temperature during the heating process. When the internal resistance value starts to rise rapidly and then drops significantly, the corresponding temperature is the film rupture temperature.
[0159] Liquid absorption test: Cut 3 pieces of 150mm x 150mm diaphragm samples and weigh them. 1 Place the sample in the electrolyte, seal and soak for 1 hour, then take it out and wipe the electrolyte on the sample surface with a dust-free cloth. Weigh the weight m 2 Liquid absorption rate = (m 2 -m 1 ) / m 1 × 100%. After the test is completed, take the average value of the test values of the three samples.
[0160] Soft pack battery K value test: Use the diaphragm sample to assemble a 5ah battery, fully charge the battery with constant current and constant voltage, and then measure the battery voltage V1 after standing for 4 hours; after standing at room temperature for 7 days, measure the battery voltage V2 again. K value = (V 1 -V 2 ) / (7×24).
[0161] Normal temperature cycle retention rate (500 weeks) test: Use the diaphragm sample to assemble a 5Ah battery cell, and cycle the battery cell at normal temperature. The cycle format is: fully charge at 1C constant current and constant voltage, and then discharge at 1C DC. Repeat this cycle and record the initial discharge capacity S 1 and the Nth cycle discharge capacity S N , Nth cycle retention rate = (S N / S 1 )×100%.
[0162] Table 2 Performance test
[0163]
[0164] Compared with Comparative Examples 5-6, Examples 1-7 are significantly improved in ion conductivity, membrane rupture temperature, liquid absorption rate, battery cell K value and cycle capacity retention rate, which can confirm that the high-porosity and large-pore core layer of the high-safety diaphragm suitable for fast charging can significantly improve the lithium ion conduction efficiency and electrolyte retention performance, improve the kinetic performance and battery cell cycle capacity retention rate; the surface layer with a low melt index (the first polypropylene layer and the third polypropylene layer) can give the high-safety diaphragm suitable for fast charging a higher membrane rupture temperature, and the higher mechanical strength can also effectively prevent the puncture of the positive and negative electrode burrs, and improve the battery cell K value.
[0165] By comparing Examples 1-3 and Comparative Example 1, changing the thickness distribution of the surface and core layers of the diaphragm has an impact on the performance of the diaphragm; increasing the surface thickness increases the rupture temperature of the diaphragm and improves safety; but the ionic conductivity is slightly reduced, and the K value is reduced, which is beneficial to improving the self-discharge of the battery cell; the liquid absorption capacity of the diaphragm is slightly reduced, resulting in a slight decrease in the cycle capacity retention rate of the battery cell.
[0166] By comparing Example 1, Examples 4-5 and Comparative Example 2, changing the melt index of the polypropylene material on the surface of the diaphragm has a significant impact on the ionic conductivity, membrane rupture temperature and K value of the diaphragm. When the melt index of the surface polypropylene material increases, the mechanical properties and melting point of the surface decrease, and the micropores become larger, resulting in an increase in the ionic conductivity of the diaphragm, a decrease in the membrane rupture temperature, and a deterioration in the K value. It can be seen that the melt index of the surface polypropylene material needs to be within an appropriate range.
[0167] By analyzing Examples 6-7, Comparative Example 1 and Comparative Example 3, it is found that changing the crystallinity of the polypropylene material on the surface of the diaphragm has a significant effect on the ionic conductivity, K value and cycle capacity retention rate of the diaphragm; when the crystallinity of the surface polypropylene material decreases, the porosity of the surface decreases, and the micropores become smaller, so the ionic conductivity of the diaphragm decreases, the self-discharge of the battery cell is suppressed, the K value is improved, but the cycle capacity retention rate decreases. It can be seen that the crystallinity of the polypropylene material cannot be too high or too low.
[0168] Example 1 and Comparative Example 7 were analyzed. When the first and third layers were changed to the second layer material, a high-porosity and large-pore diaphragm was obtained, and its liquid absorption rate and ion conductivity were improved. However, since the material was replaced with a higher melt index PP material, the strength of the diaphragm was reduced, the overall micropore diameter was too large, the lithium ion self-discharge was accelerated, and the K value deteriorated and increased.
[0169] Example 1 and Comparative Example 8 were analyzed, and the third layer was changed to the second layer material to obtain a diaphragm with a two-layer material structure. The principle is the same as that of the above-mentioned Comparative Example 7, and its liquid absorption rate and ion conductivity are improved. However, since the material is replaced with a higher melt index PP material, the strength of the diaphragm is reduced, the overall micropore diameter is too large, the self-discharge of lithium ions is accelerated, the K value deteriorates and increases, and the safety of the diaphragm is greatly reduced.
[0170] Example 1 and Comparative Example 9 are analyzed, and the second layer is replaced by the third layer material to obtain a diaphragm with low porosity and small pore size. Its puncture strength is improved, and its K value is further improved, but its liquid absorption rate and ionic conductivity are significantly reduced, and it is not suitable for fast charging system.
[0171] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0172] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A high-safety diaphragm suitable for fast charging, characterized in that: comprising a first polypropylene layer, a second polypropylene layer, and a third polypropylene layer; The second polypropylene layer is disposed between the first polypropylene layer and the third polypropylene layer; The thickness, melt index and crystallinity of the first polypropylene layer and the third polypropylene layer are each independently lower than those of the second polypropylene layer.
2. The high-safety diaphragm suitable for fast charging according to claim 1, characterized in that: At least one of the following conditions is met: A. The thickness of the first polypropylene layer and the third polypropylene layer are each independently 0.055 times to 0.33 times the thickness of the second polypropylene layer; B. the ratio of the melt index of the first polypropylene layer and the third polypropylene layer to the melt index of the second polypropylene layer is independently 1:1.25-5; C. The ratio of the crystallinity of the first polypropylene layer and the third polypropylene layer to the crystallinity of the second polypropylene layer is independently 0.92-0.98:
1.
3. The high-safety diaphragm suitable for fast charging according to claim 2, characterized in that: At least one of the following conditions is met: A. The thickness of the first polypropylene layer and the third polypropylene layer are each independently 0.08-0.25 times the thickness of the second polypropylene layer; B. the ratio of the melt index of the first polypropylene layer and the third polypropylene layer to the melt index of the second polypropylene layer is independently 1:2-4; C. The ratio of the crystallinity of the first polypropylene layer and the third polypropylene layer to the crystallinity of the second polypropylene layer is independently 0.95-0.97:
1.
4. The high-safety diaphragm suitable for fast charging according to any one of claims 1 to 3, characterized in that: At least one of the following conditions is met: A. the average radius of the micropores of the first polypropylene layer and the third polypropylene layer are independently 0.5 to 0.93 times the average radius of the micropores of the second polypropylene layer; B. The porosity of the first polypropylene layer and the third polypropylene layer is independently 0.6 to 0.95 times the porosity of the second polypropylene layer; C. The surface porosity of the first polypropylene layer and the third polypropylene layer is independently 35%-50%; D. The pore sizes of the first polypropylene layer and the third polypropylene layer are independently 20 nm to 50 nm.
5. The high-safety diaphragm suitable for fast charging according to claim 4, characterized in that: The average radius of the micropores of the first polypropylene layer and the third polypropylene layer are independently 0.7 to 0.9 times the average radius of the micropores of the second polypropylene layer.
6. The high-safety diaphragm suitable for fast charging according to claim 4, characterized in that: At least one of the following conditions is met: A. The porosity of the first polypropylene layer and the third polypropylene layer is independently 0.8 to 0.95 times the porosity of the second polypropylene layer; B. The surface porosity of the first polypropylene layer and the third polypropylene layer is independently 38%-46%; C. The pore sizes of the first polypropylene layer and the third polypropylene layer are independently 25 nm to 35 nm.
7. A method for preparing a high-safety diaphragm suitable for fast charging according to any one of claims 1 to 6, characterized in that: include: The first polypropylene layer material, the second polypropylene layer material and the third polypropylene layer material are melt-extruded to obtain a composite multi-layer cast film; The composite multilayer cast film is heat treated and stretched to obtain a high-safety diaphragm suitable for fast charging.
8. The method for preparing a high-safety diaphragm suitable for fast charging according to claim 7, characterized in that: At least one of the following conditions is met: A. The heat treatment temperature is 130°C-155°C and the time is 0.5h-3h; B. The stretching includes cold drawing, hot drawing and heat setting in sequence; The cold drawing temperature is 70°C-95°C, and the speed ratio is 1.02-1.1; The temperature of the hot drawing is 130°C-148°C, and the speed ratio is 1.9-2.2; The temperature of the heat setting is 153° C.-160° C., and the speed ratio is 0.9-0.
97.
9. A lithium ion battery, characterized in that: The invention comprises the high-safety diaphragm suitable for fast charging as described in any one of claims 1 to 6 or the high-safety diaphragm suitable for fast charging prepared by the preparation method of the high-safety diaphragm suitable for fast charging as described in claim 7 or 8.
10. An electrical device, characterized in that: Includes the lithium ion battery as claimed in claim 9.
